Performance evaluation of polyaluminium chloride in controlling fluid loss of water based mud - Dzulhaziq Wahid, 1990-, author; Mohd. Fauzi Hamid, supervisor; Fakulti Kejuruteraan Petroleum dan Tenaga Diperbaharui (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2013)
Project Paper Sarjana Muda Kejuruteraan (Petroleum) - Universiti Teknologi Malaysia, 2013